Factors associated with parents' willingness to vaccinate their children against COVID-19: The LA pandemic surveillance cohort study - Chun Nok Lam; William Nicholas; Alejandro De La Torre; Yanpui Chan; Jennifer B. Unger; Neeraj Sood; Howard Hu (AIMS Press, 2022)
Background: Children age 5-11 became eligible for COVID-19 vaccination in November 2021 in the United States, but vaccine uptake in this age group remains low. Understanding reasons why parents are hesitant to vaccinate their children may provide critical insights to help protect children from COVID-19 infection. This study examines factors associated with parents' willingness to vaccinate their children. Methods: We conducted a cross-sectional survey focusing on the Los Angeles County adult residents between March and June 2021. Our analytic sample focused on a subgroup of participants who self-report having a child. Predictors included parents' vaccination status and beliefs about COVID-19. We used multivariable logistic regression analysis and calculated the predicted probabilities of parents' willingness to vaccinate their children. Results: Parents (n = 401) who worried about catching the virus, had trust in vaccine development and the COVID-19 vaccine approval process, and vaccinated against COVID-19 were more likely to be willing to vaccinate their children. Socio-economic, racial and ethnic differences were no longer statistically significant in the adjusted model. Predicted probabilities of parents who were willing to vaccine their children were 55% among the vaccinated and 36% among the unvaccinated. Conclusions: Parents' intent to vaccinate their children is influenced by their perceived severity of the pandemic, trust in the vaccine development process, and their vaccination status, which can be the potential drivers of hesitancy to vaccinate their children.